Représenter « avec » le rite : réflexivité et danse rituelle dans un tableau murui-muina - Oscar Ivan Garcia (Journal de la Société des Américanistes)
Analyzing a painting of the Amazonian painter Brus Rubio Churay dedicated to the murui-muina ritual dances, I will show the particular link that the artist establishes between art and ritual: his painting is less a representation of the ritual and more a representation “with” the ritual. Inspired by the logic of the murui-muina ritual dances, the artist creates a mise en abyme effect mobilizing two different forms of reflexivity: one in the artist and the other in the observer. This study is based on ethnographic data collected during my doctoral fieldwork and on interviews with the artist. After presenting how the Murui-Muina define dance, their ritual balls and how this painter represents them, I will question how the artist uses “ritual condensation” to create his painting, while emphasizing the particular relationship between the canvas, the ritual and the observer.